Facade, Wakefield House - Ghosh, Ayan (2023)
Wakefield House is located on SS Ramgoolam Marg (former Sprott Road), named after the founding father of Mauritius, Seewoosagur Ramgoolam, often referred to as Chacha Ramgoolam or SSR. He served as the nation's first Prime Minister (1968-1982) and had roots in Bihar, from where his father had arrived in Mauritius as a laborer in 1896.